(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper arguesthatgrowing income andno income inequalitiesin developing Asiapose a clear and present danger to social cohesion,political stability,and therefore the sustainability of growth itself. The rapid creation of productive economic opportunities combinedwith significantly broadening accessto theseopportunities, particularly for the bypassed and marginalized, must be ensured. Progressively lifting thewell-being of a greater share of the population will contribute toward harmony